Elucidation of corrosion inhibition of metals by Agarwood leave extracts. - Rahim, Afidah Abdul (Universiti Sains Malaysia, 2017)
Corrosion is a serious problem faced that cost many industries billions of dollars. Corrosion inhibitors were thus developed to overcome the corrosion problem. The leaf extract of an agarwood producing tree (Aquilaria malaccensis) was obtained and studied as corrosion inhibitors for mild steel in HCI solution.